Revitalization of Public Passenger Cars in Bekasi Regency - Agung Sophian Pramono; Buddy Hartanto Susilo; Bambang Endro Yuwono; Dadang Muhammad (Eduvest - Journal of Universal Studies, 2025)
Transportation is a basic necessity that is crucial, especially for urban communities. Public Passenger Cars (MPU) in Bekasi Regency play a vital role in supporting the daily mobility and activities of residents. However, the current performance of MPU is still suboptimal, as indicated by loading factors, frequencies, travel times, waiting times, and headways that do not meet established standards. This study utilizes the Importance-Performance Analysis (IPA) method to assess MPU performance from the perspective of service users. The analysis results indicate the need for route reorganization from 10 to 9 routes, and a fare of Rp. 3000,00 per passenger or Rp. 700,00 per km. Key areas for improvement include room temperature regulation, fare, ease of reaching routes, stopping times, the number of operating vehicles, and vehicle age. Linear regression analysis shows that vehicle waiting time and passenger safety and security are the most influential factors.